Analysis Student Motivation and Learning Outcomes by Apllying Problem Based Learning and Discovery Learning Models - Freddy Tua Musa Panggabean; Pasar Maulim Silitonga; Jamalum Purba; Jasmidi Jasmidi; Rica Ariani Purba (Jurnal Inovasi Pembelajaran Kimia (Journal of Innovation in Chemistry Education), 2023)
Problem Based Learning and Discovery Learning are models that can increase motivation and learning outcomes of Macromedia Flash-based students on chemical equilibrium materials. The instruments used in this study are test instruments with a cognitive level of C3-C5 and non-test instruments of learning motivation questionnaires. This study aims to: 1) To determine the differences in learning outcomes with the PBL and DL models; and 2) To find a linear and significant relationship between motivatIon and student learning outcomes. The sample was 64 students of class XI MIPA 1 and MIPA 2 who were taken using random sampling techniques. Data analysis using a two-party t-test and a correlation test. The results: 1) There were differences in chemistry learning outcomes of students who were using the PBL and DL models. Where student learning outcomes obtained PBL model (18,219±2,268) and student learning outcomes using the DL model (16,438±2,327) with tvalue (3,101) > ttable (2.00) and a sig value (0.003)< sig(0.05). 2) There is a linear and significant correlation between motivation and student learning outcomes where in the PBL model obtained r count (0.773) > r table (0.349) and dl model obtained rcount (0.770) > r table (0.349) with sig(0.000) value < sig (0.05).